CFD investigation of transonic axial compressor rotor blade at various off-design conditions - Epsipha, Pauline; Zuber, Mohammad; Ahmad, Kamarul Arifin (Universiti Putra Malaysia Press, 2016)
Flow separation over blade surfaces is an important parameter and its reduction or elimination can improve better aerodynamic performance, efficiency and stall margin. In this work, numerical investigation has been carried out to study the flow separation and performance analysis of a transonic axial compressor rotor blade at off-design operating conditions. The off-design cases studied comprised of compressor operation at 80%, 90%, 100% and 105% on the on-design rotational speed. The results are validated with experimental work from literature. Additionally, 3D flow visualisations and performance parameters were examined in detail to understand the blade to blade relative mach number distributions and shock front created by the model. Finally, the benefits of unsteady simulation on axial compressor blade performance predictions were examined.